The Formation of a Stable Technopolitical Environment as a Factor in the Development of Recursive Public Policy in Russia - A. M. Kaplunenko (Управленческое консультирование, 2022)
Aims. Conceptualization of technopolitical sphere impact on recursive processes of public policy; defining key problems that inhibit public authorities from improving digital politics stability essential for developing public policy recursive potential.Methods. The work is based on institutional approach traditional for conducting interdisciplinary research about using informational and communicative technologies in politics and governance. Moreover, it is helpful for considering meaning of public institutes in the scope of conceptualization of technopolitical sphere stability and recursiveness as an attribute of public policy.Results. Recent approaches to understanding the essence of public policy define the efficiency of shaping political agenda, developing and making decisions as more and more dependent on expert knowledge and ways of political participation. Based on the recursiveness as a public policy attribute there is made a point of expert knowledge for building and keeping feedback linking between system elements as a key principle of public policy change as an «epistemic thing». Recursive processes progression depends on stability of technopolitical sphere that rests upon quality, direction and dynamics of institutional change, political inclusiveness. As for Russia, building technopolitical infrastructure necessary for recursive processes is in progress now and meet a wide range of political and governmental rigidity, legal framework insufficiency. In order to overcome it, public authorities shall pay attention to total improving the digital literacy, coordination, legal framework update and developing new institutes of digital intersectoral collaboration.Conclusion. In public policy and its actors recursiveness serves as a principle of systematic monitoring politics and governance which defines evolutional dynamics of these processes. Digital politics creates conditions for building recursive processes into the context of shaping political agenda, developing and making decisions. The research results highlight issues significant for contemporary political science in the context of technopolitical national development and can be enhanced with both theoretical and applied research.